Zooplankton as an Indicator: A Dramatic Shift in Its Composition Following a Sudden Temporal Brownification of a Tropical Oligotrophic Lake in Southern Mexico - Manuel Elías-Gutiérrez; Martha Valdez-Moreno; Lucia Montes-Ortiz; Alma E. García-Morales (Diversity)
Lake Bacalar, a fragile oligotrophic ecosystem located in the southeast of Yucatan Peninsula, Mexico, suffered from a sudden brownification after the tropical storm Cristobal in June 2020 in the Gulf of Mexico. The color change was the most visible effect of the storm, but all other water variables changed towards eutrophication. We used light traps and DNA barcoding of the zooplankton specimens based on previous baseline constructed for comparison with the species found after the change. A dramatic shift in the zooplankton community occurred: biomass was reduced to a minimum and 20 species of water mites, five copepods, three cladocerans, three chironomids and six species of fish larvae disappeared for a period of at least one year. They were replaced by three species of water mites, four cladocerans, one copepod, 23 chironomids and one ephemeropteran previously not registered, most of the species being characteristic of more eutrophic environments. The southernmost part of the lake, Laguna Xul-Ha, which conserved its oligotrophic characteristics, apparently became a refuge for the original fauna from the whole system. The ecosystem did not fully recover to its original condition until about two years later. While the system has returned to its original state after the storm described here, future changes in land use, including unsustainable tourism expansion, may compromise its resilience and induce hysteresis.